2023
DOI: 10.20517/evcna.2023.13
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic proteins in neuron-derived extracellular vesicles as biomarkers for Alzheimer’s disease: novel methodology and clinical proof of concept

Abstract: Aims: Blood biomarkers can improve drug development for Alzheimer’s disease (AD) and its treatment. Neuron-derived extracellular vesicles (NDEVs) in plasma offer a minimally invasive platform for developing novel biomarkers that may be used to monitor the diverse pathogenic processes involved in AD. However, NDEVs comprise only a minor fraction of circulating extracellular vesicles (EVs). Most published studies have leveraged the L1 cell adhesion molecule (L1CAM) for NDEV immunocapture. We aimed to develop and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Unlike proBDNF, mature BDNF showed no differences between groups. These findings are in agreement with the study by Eitan et al (2023) , in which levels of NDEV-associated proBDNF were also found lower in AD compared to control individuals and were positively correlated with MMSE scores. Our results, also, indicate that levels of NDEV-associated proBDNF may reflect true relative concentrations in brain cells, since similar decreases in MCI and AD dementia compared to the cognitively normal state were found in an autopsy study using cerebral tissue samples ( Peng et al, 2005 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Unlike proBDNF, mature BDNF showed no differences between groups. These findings are in agreement with the study by Eitan et al (2023) , in which levels of NDEV-associated proBDNF were also found lower in AD compared to control individuals and were positively correlated with MMSE scores. Our results, also, indicate that levels of NDEV-associated proBDNF may reflect true relative concentrations in brain cells, since similar decreases in MCI and AD dementia compared to the cognitively normal state were found in an autopsy study using cerebral tissue samples ( Peng et al, 2005 ).…”
Section: Discussionsupporting
confidence: 93%
“…Plasma aliquots were received and processed blindly by investigators at the National Institute on Aging, Baltimore, MD. NDEVs were isolated following a two-step procedure based on previous studies by our group and others validating L1 Cell Adhesion Molecule (L1CAM), the axonal protein Growth-Associated Protein 43 (GAP43), and the neuron cell surface protein Neuroligin 3 (NLGN3) as targets for the immunocapture of NDEVs from plasma ( Kapogiannis et al, 2019 ; Eitan et al, 2023 ). Slight differences between the protocol employed here and that described by Eitan et al include the isolation of crude plasma EVs via size exclusion chromatography (SEC) instead of polymer-based sedimentation, and targeting the neuronal surface proteins GAP43 and NLGN3, in addition to L1CAM, for the immunocapture of NDEVs, expected to increase the purity and yield of recovered NDEVs, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Also, a subsequent study showed that anti-L1CAM antibody clone UJ127 does not elute with EVs isolated by size-exclusion chromatography [22], exists mostly in soluble forms and cross-reacts with antibodies employed for biomarker quantification. For these reasons, many groups have been exploring alternative neuronal markers, such as ATP1A3 [80], GAP43, and NLGN3 [131], GABRD and GPR162 [81] and NRXN3 [163]. Meanwhile, markers like GLAST1 are sometimes employed to enrich speculative astrocytic EVs.…”
Section: Resultsmentioning
confidence: 99%
“…Although western blotting of typical EV markers has been extensively used to characterize EVs isolated from different biofluids and cell-cultured media, the low recovery of specific cell-derived EVs, including BDEs, limits its utility, especially when isolated from human biofluids. Still, the expression of neuron-specific markers, such as L1CAM, SNAP25, NeuN, and GluR2, as well as general EV markers, like CD9, Flot-1, CD9, and TSG101, has been confirmed by western blotting in many studies ( Dagur et al, 2019 ; Serpente et al, 2020 ; Saeedi et al, 2021 ; Eitan et al, 2023 ). Similarly, the expression of typical EV markers, like Alix, flotillin-1, Annexin-A2, and CD81, has been reported in ADEs isolated from cultured astrocytes media ( Pascua-Maestro et al, 2019 ; D’Arrigo et al, 2021).…”
Section: Characterization Of Brain Cell–derived Extracellular Vesicle...mentioning
confidence: 96%
“…BDEs have been extensively characterized for their concentration (particle number per ml), size distribution, expression of EV biomarkers, and cargos (protein, metabolites, and nucleic acids) to identify disease-specific biomarkers ( Goetzl et al, 2015b , 2016b ; Doyle and Wang, 2019 ; Kumar et al, 2021a , 2022 , 2023 ; Eitan et al, 2023 ) ( Fig. 3 ).…”
Section: Characterization Of Brain Cell–derived Extracellular Vesicle...mentioning
confidence: 99%